Transformation of Roadworthiness and Motor Vehicle Certification Testing Centers into Public Service Agencies: A Strategy for Improving Vehicle Testing Services in the Era of Globalization - Suherlan, Ence (International Publisher, 2022)
One of the public services that has a big impact on people's daily lives is transportation. Smooth and safe transportation is one of the backbones of the national economy and social welfare. The new BLU status given to BPLJSKB must be used as momentum to make improvements from within. This status must be used to increase service capacity, modernize infrastructure, and strengthen human resource competencies. In this research, the most appropriate approach is literature study. This approach allows researchers to understand the context, background and theoretical implications of changing the status of BPLJSKB to BLU by referring to existing literature. In other words, the transformation of BPLJSKB into BLU is not just an administrative step, but a strategic step to ensure that this institution remains relevant, effective, and provides maximum value to society. This capacity development is a response to the demands of the times for public institutions to work to higher standards and always be oriented towards the public interest.